Is the recovery of stratospheric O3 speeding up in the Southern Hemisphere? An evaluation from the first IASI decadal record (2008–2017) - C. Wespes; D. Hurtmans; S. Chabrillat; G. Ronsmans; C. Clerbaux; C. Clerbaux; P.-F. Coheur (Atmospheric Chemistry and Physics, 2019)
In this paper, we present the global fingerprint of recent changes in middle–upper stratosphere (MUSt; <25 hPa) ozone (O3) in comparison with lower stratosphere (LSt; 150–25 hPa) O3 derived from the first 10 years of the IASI/Metop-A satellite measurements (January 2008–December 2017). The IASI instrument provides vertically resolved O3 profiles with very high spatial and temporal (twice daily) samplings, allowing O3 changes to be monitored in these two regions of the stratosphere. By applying multivariate regression models with adapted geophysical proxies on daily mean O3 time series, we discriminate anthropogenic trends from various modes of natural variability, such as the El Niño–Southern Oscillation (ENSO). The representativeness of the O3 response to its natural drivers is first examined. One important finding relies on a pronounced contrast between a positive LSt O3 response to ENSO in the extratropics and a negative one in the tropics, with a delay of 3 months, which supports a stratospheric pathway for the ENSO influence on lower stratospheric and tropospheric O3. In terms of trends, we find an unequivocal O3 recovery from the available period of measurements in winter–spring at middle to high latitudes for the two stratospheric layers sounded by IASI (>∼35<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="32pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="1f3790cd2a78935fb7cb975bec888106"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-14031-2019-ie00001.svg" width="32pt" height="10pt" src="acp-19-14031-2019-ie00001.png"/></svg:svg>∘ N–S in the MUSt and >∼45<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="32pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="6eccbbdab7ba7abfcfc34b4448a803da"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-14031-2019-ie00002.svg" width="32pt" height="10pt" src="acp-19-14031-2019-ie00002.png"/></svg:svg>∘ S in the LSt) as well as in the total columns at southern latitudes (>∼45<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="32pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="291dda3e49aa3d5ec2fc944845a8c16c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-14031-2019-ie00003.svg" width="32pt" height="10pt" src="acp-19-14031-2019-ie00003.png"/></svg:svg>∘ S) where the increase reaches its maximum. These results confirm the effectiveness of the Montreal Protocol and its amendments and represent the first detection of a significant recovery of O3 concurrently in the lower, in the middle–upper stratosphere and in the total column from one single satellite dataset. A significant decline in O3 at northern mid-latitudes in the LSt is also detected, especially in winter–spring of the Northern Hemisphere. Given counteracting trends in the LSt and MUSt at these latitudes, the decline is not categorical in total O3. When freezing the regression coefficients determined for each natural driver over the whole IASI period but adjusting a trend, we calculate a significant speeding up in the O3 response to the decline of O3-depleting substances (ODSs) in the total column, in the LSt and, to a lesser extent, in the MUSt, at high southern latitudes over the year. Results also show a small significant acceleration of the O3 decline at northern mid-latitudes in the LSt and in the total column over the last few years. That, specifically, needs urgent investigation to identify its exact origin and apprehend its impact on climate change. Additional years of IASI measurements would, however, be required to confirm the O3 change rates observed in the stratospheric layers over the last few years.